Spatial price transmission from the international market to the Mexican milk market - Martínez-Marcos, Diana; Barrios-Puente, Gerónimo; Pérez-Soto, Francisco; Ruiz-Hernández, Jaime Antonio; Lara-Reimers, Eduardo Alberto (Ecosistemas y Recursos Agropecuarios, 2023)
Mexico imports approximately 25% of the milk consumed in the country, this quantity is comparable to 30% of domestic production. Because of this, the Mexican producer price might be influenced by the international price of milk. Therefore, the purpose of this research was to analyze price transmission between the international market and the Mexican milk market in the national, regional (Jalisco), and municipal (Chicontepec, Veracruz) scope. For this, stationarity of the series was determined using the Augmented Dickey-Fuller test, cointegration was examined using the Johansen test, and an error correction model and an asymmetric error correction model were estimated. The results indicate that milk producer prices in Mexico are cointegrated with the Oceania, the European Union, and the United States prices, being the latter the ones that have the greatest effects on the producer price in Mexico and are transmitted in a symmetric way to the Mexican market. Besides, it was found that the speed of adjustment of the producer price in the event of deviations from equilibrium is superior for the regional scope, followed by the national and the municipal local. Meaning that the variations of the international price affect the Mexican milk producers in a different way.